Barriers to acute stroke care at a tertiary hospital in the Western Cape - Matshikiza, Wonga (Department of Medicine, 2020)
Background Stroke guidelines recommend treatment of acute stroke as a medical emergency. In many countries prolonged delays occur before patients with acute stroke receive medical attention. Only a small percentage of patients are assessed in hospital within the time window for reperfusion therapy. There is limited available published data concerning barriers to acute stroke care in South African patients. The aim of this study was to determine the pre-hospital barriers and in-hospital delays to emergency care for patients presenting to Groote Schuur Hospital (GSH) with acute stroke.